NiW catalyst modified with C12A7-H− and its promotion to hydrogenation selectivity of hydrodesulfurization. (15th April 2021) - Liu, Xuandong; Li, Lei; Sun, Huayang; Wen, Guangming; Wang, Dan; Ren, Shenyong; Guo, Qiaoxia; Zhang, Wencheng; He, Shengbao; Shen, Baojian
Graphical abstract: Highlights: C12A7-H − containing active H species is successfully synthesized. More Ni-W-S species and higher sulfidation degree are obtained. C12A7-H − improves the reaction rate constants and turnover frequencies. Lower Lewis acid sites and rim/edge ratios are observed by adding C12A7-H − . The transfer of active H species from C12A7-H − may increase HYD/DDS ratios. Abstract: [Ca24 Al28 O64 ] 4+ ·4(H − ) (abbreviated as C12A7-H − ) powder containing H − species was synthesized to modify NiW catalyst. The incorporation of C12A7-H − increases the reaction rate constants and turnover frequencies of NiW catalysts in hydrodesulfurization (HDS) of dibenzothiophene (DBT). The characterization results show that the introduction of C12A7-H − promotes the reducibility of NiW catalysts, resulting in higher sulfidation degree and more Ni-W-S species. In spite of the fact that rim/edge sites ratios and Lewis acid sites are decreased, the introduction of C12A7-H − still increases the hydrogenation/direct desulfurization ratios of NiW catalysts in HDS of DBT. Furthermore, higher HDS rates of C12A7-H − modified NiW catalysts are also observed in HDS of 4, 6-dimethyldibenzothiophene. These can be attributed to C12A7-H − material that may transfer active H species to NiW catalysts and thereby promote the hydrogenation selectivity of NiW catalyst.